Natural resources, multinational companies and national projects: Multinationals as the “necessary other” in Latin America (1900-1954) - Conejo Barboza, Luis (2021)
This article seeks to study the conflict that originated the representation of nature exercised between multinational companies in the United States and the nationalism of the Latin American countries developed between the years 1900 - 1954. Most of the existing studies on nationalism focus on analyzing the political and educational aspects in the formation of the nationalist discourse, similarly, the studies of the representation of nature by the national states, have focused on the focus and category of environmental conflicts. What this work proposes is to study how the representation of nature could generate certain conflicts between national interests and the interests of some multinational companies, making it clear that the relationship between these actors was extremely dynamic.